2016
DOI: 10.7555/jbr.30.20150059
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-V gene therapy for disease prevention / treatment:a critical analysis

Abstract: Apolipoprotein (apo) A-V is a novel member of the class of exchangeable apo's involved in triacylglycerol (TG) homeostasis. Whereas a portion of hepatic-derived apoA-V is secreted into plasma and functions to facilitate lipo­protein lipase-mediated TG hydrolysis, another portion is recovered intracellularly, in association with cytosolic lipid droplets. Loss of apoA-V function is positively correlated with elevated plasma TG and increased risk of car­diovascular disease. Single nucleotide polymorphisms (SNP) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 54 publications
(49 reference statements)
0
2
0
1
Order By: Relevance
“…Knockdown APOA5 gene in mice confers a four-fold increase of plasma TG levels, whereas high-expression of the human APOA5 gene in mice leads to a decrease of TG by approximately 50% [ 60 ]. Moreover, human genetic studies have identified several APOA5 SNPs affected plasma TG levels [ 61 ]. Inherited deficiency of the APOA5 gene in humans leaded to severe hypertriglyceridemia.…”
Section: The Mechanism Of Apoa5 In Modulating Obesity and Metabolic Smentioning
confidence: 99%
“…Knockdown APOA5 gene in mice confers a four-fold increase of plasma TG levels, whereas high-expression of the human APOA5 gene in mice leads to a decrease of TG by approximately 50% [ 60 ]. Moreover, human genetic studies have identified several APOA5 SNPs affected plasma TG levels [ 61 ]. Inherited deficiency of the APOA5 gene in humans leaded to severe hypertriglyceridemia.…”
Section: The Mechanism Of Apoa5 In Modulating Obesity and Metabolic Smentioning
confidence: 99%
“…Несколько апо-липопротеинов, включая Апо А4, Апо А5, Апо С3 и Апо Е, могут влиять на липидный обмен при НАЖБП [29]. При этом полиморфизмы генов аполипопротеи-нов были обнаружены у пациентов с НАЖБП [30,31].…”
Section: атерогенная дислипидемияunclassified
“…53 For instance, in 313 patients with FH who were evaluated using a targeted next-generation sequencing panel and an assay to detect large-scale copy-number variation, Wang et al 54 found a genetic basis for extremely elevated LDL-C in ≈67% of patients. Of these individuals, 45% had a monogenic largeeffect variant, 6% had a copy-number variation, and 17% had a strong polygenic component, as defined by accumulation of common GWAS-identified SNPs associated with LDL-C levels.…”
Section: Advances In Genetic Dyslipidemiasmentioning
confidence: 99%